A Recent Literature Review on the Use of IoT in Medical Logistics - Lubis, Rinaldi; Haviana, Evan; Hardi, Yuni (YCMM, 2025)
The Internet of Things (IoT) has emerged as a transformative technology in the healthcare sector, offering significant advantages for improving the efficiency and reliability of medical logistics. This study presents a systematic literature review of recent research (2020–2025) focused on the application of IoT in medical logistics. A total of 200 studies were initially identified, and through a structured selection process using the PRISMA framework, six articles were ultimately included for in-depth analysis.The findings highlight that IoT technologies are widely applied in areas such as cold chain monitoring, inventory tracking, real-time asset management, and integration with blockchain and cloud platforms. These applications improve data accuracy, reduce product spoilage, and enhance traceability. However, challenges such as high implementation costs, system interoperability, and data security risks persist, especially in low-resource settings.This review provides a comprehensive overview of the current state of IoT implementation in medical logistics and offers insights for future research and policy development. The study concludes that a multidisciplinary and collaborative approach is essential to realize the full potential of IoT in creating responsive and secure healthcare supply chains.